Empowering Cadres Through the Practice of Processing and Providing MP ASI in the Context of Stunting Prevention - Yessi Marlina; Dewi Erowati; Yuliana Arsil (Universitas Lancang Kuning, 2023)
Giving complementary feeding properly is not only to meet children's nutritional needs but also to stimulate children's eating skills. However, there are still many inappropriate complementary feeding practices, due to the lack of knowledge of mothers and the lack of available information. The cadres of Integrated Healthcare Centre (POSYANDU) as an extension of health workers are expected to be able to provide mothers with adequate information and skills regarding the proper practice of giving and processing complementary feeding. The purpose of this community service is to increase the knowledge of cadres regarding the practice of giving complementary feeding and the skills of cadres in processing the menu of complementary feeding. This community service involved 30 posyandu cadres in Rejosari Village. Activities carried out in the form of counseling accompanied by the practice of menu processing. Based on the results of the evaluation, the knowledge level of cadres has increased, which means that the cadres are considered to have understood and have been able to disseminate information related to proper complementary feeding practices and have been able to process the menu.